Cochlear effects of intraoperative use of Mesna in cholesteatoma surgery - Vincenti, Vincenzo; Magnan, Jacques; Zini, Carlo (Acta Biomedica Atenei Parmensis, 2014)
Background and aim: Mesna is thiol compound proposed as chemical dissector in otolaryngologic surgery. The aim of this study was to address the issue of possible ototoxicity from topical administration of MESNA into the middle ear during otologic surgery. Methods: Audiological findings of patients (n=55) who underwent canal wall up tympanomastoidectomy with the ancillary use of Mesna in 1-year period were retrospectively reviewed. We identified another set of 51 patients who had undergone otologic surgery without the use of Mesna to serve as a control group. Preoperative and postoperative mean bone conduction thresholds were calculated and compared between the two groups for the frequencies of 500,1000,2000, and 3000; 4000 and 8000 Hz were further analyzed to search for high-frequency sensorineural hearing loss. Results: Fifty-five patients were operated on with the ancillary use of Mesna and 51 underwent surgery with traditional mechanical dissection alone. When mean preoperative bone conduction values were compared with postoperative values, no significant differences were found for any of the frequencies tested in both groups. Analyzing changes in bone conduction at 4000 and 8000 Hz a slight worsening was observed in both groups. Conclusions: We found no difference in hearing thresholds between the treatment and control groups. Thus, the results of this study confirmed data obtained in laboratory animal models demonstrating that intraoperative use of Mesna in middle ear surgery is safe and does not lead to ototoxic effects.